2020
DOI: 10.1002/jimd.12245
|View full text |Cite|
|
Sign up to set email alerts
|

Long‐term survival outcomes of patients with Niemann‐Pick disease type C receiving miglustat treatment: A large retrospective observational study

Abstract: Miglustat has been indicated for the treatment of Niemann‐Pick disease type C (NP‐C) since 2009. The aim of this observational study was to assess the effect of miglustat on long‐term survival of patients with NP‐C. Data for 789 patients from five large national cohorts and from the NPC Registry were collected and combined. Miglustat‐treated and untreated patients overall and within sub‐groups according to age‐at‐neurological‐onset, that is, early infantile‐onset (<2 years), late infantile‐onset (2 to <6 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 23 publications
5
29
0
3
Order By: Relevance
“…It has been reported to slow neurological deterioration and improve survival in different NPC cohorts [ 42 , 84 , 87 , 88 ]. Recently, a large retrospective observational study that used a multinational registry and five large national cohorts suggested that miglustat effect was statistically significant in improving the survival of LIF and juvenile patients, but not those in EIF group [ 89 ]. We could not obtain sufficient data on the miglustat use in the EIF group reviewed here to comment on its effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to slow neurological deterioration and improve survival in different NPC cohorts [ 42 , 84 , 87 , 88 ]. Recently, a large retrospective observational study that used a multinational registry and five large national cohorts suggested that miglustat effect was statistically significant in improving the survival of LIF and juvenile patients, but not those in EIF group [ 89 ]. We could not obtain sufficient data on the miglustat use in the EIF group reviewed here to comment on its effect.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 42% (16/38) of the dysregulated genes encode sphingolipid-binding proteins [57] (Figure 8). Sphingosine and sphingolipids accumulate in NPC1 and have been proposed to contribute to NPC pathology [58][59][60], and miglustat, a glycosphingolipid synthesis inhibitor, has shown efficacy in slowing NPC1 disease progression [61,62]. In contrast to the high fraction of sphingolipid-binding proteins, only three of the dysregulated genes (Apoe, Ctsd, and Cd63) encode proteins were shown by Hulce et al [63] to interact with cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…A hatóanyag átjut a vér-agy gáton, így nemcsak a perifériás szervek, hanem a központi idegrendszer szfingolipid-anyagcseréjére is kedvező hatású, lassítja a neurológiai tünetek progresszióját [14,15]. A terápiától elsősorban a késői kezdetű formákban várható kedvező hatás [14,15]. A miglusztat mellékhatásai között enyhe-közepes súlyosságú gastrointestinalis tünetek (hasmenés, flatulentia), súlyvesztés és tremor szerepelnek.…”
Section: Megbeszélésunclassified
“…A miglusztat mellékhatásai között enyhe-közepes súlyosságú gastrointestinalis tünetek (hasmenés, flatulentia), súlyvesztés és tremor szerepelnek. A leggyakoribb mellékhatás a hasmenés, amely antipropulzív szerekkel (például loperamid), illetve az étkezési szokások megváltoztatásával, esetleg dóziscsökkentéssel rendszerint uralható [14,15]. A miglusztatkezeléssel a terápiarezisztens pszi-chiátriai tünetek is visszafordíthatók, így a terápia alkalmazása a betegség előrehaladott formáiban is javasolt [15].…”
Section: Megbeszélésunclassified
See 1 more Smart Citation